Second messenger-mediated adjustment of bacterial swimming velocity - Böhm, Alex; Kaiser, Matthias; Li, Hui; Spangler, Christian; Kasper, Christoph Alexander; Ackermann, Martin; Kaever, Volkhard; Sourjik, Victor; Roth, Volker; Jenal, Urs (Cell, 2010)
Bacteria swim by means of rotating flagella that are powered by ion influx through membrane-spanning motor complexes. Escherichia coli and related species harness a chemosensory and signal transduction machinery that governs the direction of flagellar rotation and allows them to navigate in chemical gradients. Here, we show that Escherichia coli can also fine-tune its swimming speed with the help of a molecular brake (YcgR) that, upon binding of the nucleotide second messenger cyclic di-GMP, interacts with the motor protein MotA to curb flagellar motor output. Swimming velocity is controlled by the synergistic action of at least five signaling proteins that adjust the cellular concentration of cyclic di-GMP. Activation of this network and the resulting deceleration coincide with nutrient depletion and might represent an adaptation to starvation. These experiments demonstrate that bacteria can modulate flagellar motor output and thus swimming velocity in response to environmental cues.
Gesehen am 01.02.2023